Nature - "Flegg, Jim" (Wayland, Hove, 1992)
Part of a series of books that take the reader on a journey through areas of interest. This book looks at nature, introducing the natural world of plants and animals and their habitats, as well as a range of current ecological issues. Other book in this series look at space and inventions.